Qualidade hídrica e morfometria da microbacia do córrego da Fazenda Glória, Taquaritinga-SP - Silva, Michele Cláudia da [UNESP] (2014)
This study aimed to analyze morphometric the basin, evaluate the spatial and temporal dynamics of physical-chemical parameters of water drainage network and its influences to production systems located on the slopes of the watershed of Córrego da Fazenda Glória, Taquaritinga, SP, in order to verify the environmental change from the use / land cover and the trophic status of waters. Seven watersheds were selected (M1 to M7) and four points at the mouth (F1 to F4), to collect water and land use analysis, the two-year period (August 2010 to July 2012). The variables analyzed were: temperature (TºC), pH, electrical conductivity (EC), total dissolved solids (TDS), turbidity (T), dissolved oxygen (DO), the concentration of phosphorus (P) Total and the trophic state of the resource water. The data were subjected to multivariate statistical analysis, except the match, which was analyzed by descriptive analysis. The monitoring of water resources showed a close relationship between the SDT and EC variables, more evident in relation to M2 watershed environment. The cane sugar cultivation in most of the points was predominant, followed by wetlands or floodplains. The degree of eutrophication was eutrophic to hypereutrophic. Multivariate analysis showed that the proportion of the total variance retained in the first two factors was 70.79% (CP1 = 39.08%; CP2 = 31.71%). The CP1 factor showed a positive correlation between SDT and EC variables, showing runoff process. The CP2 factor negatively correlated to the T ...